Cleonini (Coleoptera: Curculionidae: Lixinae) are monophyletic and flightless: tribe overview, rampant adult homoplasy and illustrated global diversity - Arzanov, Yuri G.; Grebennikov, Vasily V. (Zootaxa, 2017)
We summarize knowledge of the weevil tribe Cleonini worldwide, including its monophyly, relationships, distribution, biology, immature stages, economic significance and paleontology. We score adult morphological characters for 79 of a total of 96 extant genus-group Cleonini taxa considered valid to date. The resulting matrix contains 121 parsimoniously informative characters scored for 145 ingroup (Cleonini) and 29 outgroup terminals. Maximum Parsimony (MP) and Bayesian Inference (BI) analyses consistently recover monophyletic Lixinae and Cleonini. Relationships within the latter remain unresolved with either 47 (BI) or 37 (MP) branches radiating from the tribe’s most recent common ancestor. Most of the speciose genera of Cleonini emerge as monophyletic in both BI and MP analyses (generic names followed by the number of terminals, then by BI posterior probability / MP bootstrap): Adosomus (5, 94/77), Asproparthenis (6, 99/98), Chromonotus (6, 98/85), Cleonis (3, 64/76), Coniocleonus (10, 95/41), Conorhynchus (5, 95/51), Cyphoclenus (4, 65/76), Maximus (4, 84/68), Mecaspis (4, 95/91), Scaphomorphus (4, 90/84), Temnorhinus (8, 99/62) and Xanthochelus (6, 84/71). The genera Pseudocleonus (6, -/26) and Stephanocleonus (22, -/23) are not recovered in BI and weakly supported in MP. No genera are here added to, or removed from, Cleonini. We suggest that adult morphology of Cleonini was subject to widespread homoplasy obscuring the phylogenetic signal of morphological characters. Unlike the rest of Lixinae, all extant Cleonini are hypothesised to be flightless, even though often being macropterous. All 145 ingroup terminals are illustrated in three standard views; images of the type species of 15 of the 17 genus-group taxa that are not represented in our analysis are provided.